Handel's singers from the London choirs. (13th July 2021) - Burrows, Donald
Abstract: Handel's musical career in London was largely centred on the theatre—the annual seasons of operas and oratorios, and their performers, often dominated by castratos and sopranos. There was, however, an alternative strand to his creative achievement that related to the singers who held posts in London's major ecclesiastical choirs—the Chapel Royal, Westminster Abbey and St Paul's Cathedral—with particular strengths in alto and bass voices, and treble soloists. This relationship stretched from his first years in London, including the 'Utrecht' canticles, to the Thanksgiving service and the Foundling Hospital Anthem in 1749. Handel seems to have developed a social relationship with the choir musicians during his first years in London, and his music for the Chapel Royal bears evidence to the musical skills of singers such as the alto Francis Hughes and the bass Samuel Weely. Although these singers formed an independent professional circuit, there were some overlaps in personnel, as for example the tenor John Beard, who had been trained in the Chapel Royal but developed a career as a theatre and concert singer, and the bass Robert Wass, who sang as an oratorio soloist for Handel while also serving as a regular member of the choirs. The ensemble of singers was influential (via, for example, the Coronation Anthems) in the development of chorus movements as a characteristic element in Handel's theatre oratorios. The choir members also contributed directly as chorus singers for his oratorios, particularly in his later years, and he had similar reliance on 'church' singers for his oratorio performances at Oxford and Dublin.